Associations between Bone, Fat Tissue and Metabolic Control in Children and Adolescents with Type 1 Diabetes Mellitus - Wędrychowicz, A.; Stec, M.; Sztefko, K.; Starzyk, J. B. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Aims: To investigate the relationship between bone-derived osteocalcin (OC), osteoprotegerin (OPG), Receptor Activator of Nuclear Factor NF-ĸB ligand (RANKL), and fat tissue-derived leptin and adiponectin with a clinical outcome of type 1 diabetes mellitus (T1DM) in children and adolescents.Methods: 78 patients (43 girls and 35 boys), aged 11.5±4.3 years with T1DM and 11 age- and BMI-matched controls were included into the study. Patients were divided into 3 groups according to HbA1c level, I – below 7% [53 mmol/mol], II – 7–9% [53–75 mmol/mol] and III – above 9% [75 mmol/mol]. Blood samples for biochemical measurements were drawn at 8.00 AM, when the patients were in a fasting state. HbA1c was measured by the standardized IFCC method. OC, OPG, RANKL, leptin and adiponectin were measured by ELISA. ANOVA, and multiple regression analysis were used for statistical analysis.Results: Significant differences in leptin and osteocalcin levels between groups with different HbA1c values were observed (p=0.03, p=0.04). Multiple regression analysis adjusted for age showed that serum OC and leptin negatively correlated with HbA1c levels (r=−0.22, p=0.004 and r=−0.27, p=0.0001, respectively). In contrast, serum OPG correlated positively with HbA1c (r=0.26, p=0.02) as well as with adiponectin (r=0.26, p=0.02) and RANKL (r=0.27, p=0.02) levels. The correlation of OC with HbA1c was the strongest in group I – patients with good metabolic control of DM (r=−0.43, p=0.03). In that group, in multiple regression analysis adjusted for age and BMI leptin correlated positively with daily dose of insulin (r=0.52, r=0.009). In group II and III in multiple regression analysis adjusted for age and BMI OC correlated negatively with leptin (r=−0.37, p=0.01).Conclusions: Our data suggest significant relationships between bone, fat tissue and glucose metabolism in pediatric patients with T1DM. The results can confirm that poor metabolic control is associated with reduced bone formation. On the other hand fat and bone tissue can influence glucose metabolism, potentiality in insulin-dependent manner. From these data leptin or OC may be potentially used as additional therapeutic agents for T1DM.
Keywords: diabetes mellitus type 1; leptin; osteocalcin; OPG-RANKL; children and adolescents